Translanguaging Practices in Second Language Education and Their Implications for Multilingual Language Policy - Zafira Ayu Kirana; Ravindra Mahesa Putra; Nayla Qistina (LIER: Language Inquiry & Exploration Review, 2026)
Purpose: This study aims to examine the forms and pedagogical functions of translanguaging practices in second language classrooms and to analyze their implications for multilingual language policy. It seeks to bridge micro-level classroom interactions with macro-level institutional language ideologies. Subjects and Methods: The study employed a qualitative case study design conducted in a multilingual second language education program. Participants included six second language teachers and eighteen lower-intermediate to intermediate students. Data were collected through 18 classroom observations, semi-structured interviews with teachers and students, and analysis of institutional language policy documents. Data analysis involved thematic analysis, qualitative discourse analysis, and critical language policy analysis to ensure triangulation and analytical rigor. Results: Findings revealed that translanguaging was a frequent and systematic classroom practice rather than an incidental occurrence. Four dominant forms were identified: teacher-led pedagogical code-switching, peer code-mixing, meaning clarification, and affective-relational use. Translanguaging served multiple pedagogical functions, including cognitive scaffolding, conceptual reinforcement, classroom management, identity affirmation, and increased learner participation. Interview data confirmed that teachers used translanguaging intentionally to enhance comprehension and instructional efficiency, while students perceived it as supportive of understanding, confidence, and engagement. However, a clear tension emerged between effective classroom practices and monolingual-oriented institutional policies that lacked explicit recognition of translanguaging. Conclusions: The study concludes that translanguaging is an effective and legitimate pedagogical resource in second language education. To optimize its benefits, language policies should be realigned to acknowledge and support multilingual classroom realities.